Seasonal Variations in the Composition and Distribution of Planktonic Fauna in the Eastern Lagos Lagoon, Nigeria - AS Yakup; KJ Balogun; GE Ajani; KO Renner; BO Bello; JA Nkwoji; JK Igbo (Journal of Applied Sciences and Environmental Management)
The composition and distribution of planktonic fauna (adult form of zooplankton and planktonic juvenile forms of higher animals) within the eastern part of the Lagos Lagoon were investigated in July, 2008 and March, 2009 representing rainy and dry season respectively. Samples of water and planktonic fauna were collected from twelve stations within the eastern axis of the Lagoon and analyzed using standard methods. The study area had brackish water characteristics with fresh water condition (0‰ salinity across the 12 stations) in the rainy season whereas the salinity ranged from 11.4‰ to 30.5‰ in the dry season. The adult forms zooplankton recorded in the rainy season were mainly Crustaceans, Chaetognathans and Rotifers while those collected during dry season belonged to Crustacean, Cnidaria and Chordata. Crustaceans dominate both adult zooplankton and planktonic juvenile fauna in the two seasons. The rainy season adult zooplankton count (515) was lower than that of dry season (580) but the reverse was the case for the juvenile stages count (520 and 325 in rainy and dry season respectively). Higher species abundance was recorded for both adult zooplankton (20) and juvenile stages (10) in rainy than dry season when 14 and 8 were recorded for the two groups respectively. Higher values were also of community structure indices (Margalef species richness and Shannon-Wiener species diversity) were recorded in the rainy than dry season for the two groups of planktonic fauna. The findings show the influence of salinity gradients on distribution of planktonic fauna of the Lagos Lagoon. @JASEM